The Everafter War - Buckley, Michael; Ferguson, Peter, 1968- (New York : Amulet Books, 2009)
After their parents awake from a sleeping spell, Daphne and Sabrina become caught in the middle of a war between the Scarlet Hand and Prince Charming's Everafter army and learn a shocking secret about a deadly enemy.
Keywords: Characters in literature -- Juvenile fiction; Sisters -- Juvenile fiction; Magic -- Juvenile fiction; War -- Juvenile fiction; Mystery fiction; Fantasy fiction